Synovial pathology detected on ultrasound correlates with the severity of radiographic knee osteoarthritis more than with symptoms - Hall, Michelle C.; Doherty, Sally; Courtney, Philip; Latief, Khalid; Zhang, Weiya; Doherty, Michael (Elsevier, 2014)
OBJECTIVE: To [1] compare the frequency and severity of ultrasound (US) features in people with normal knees (controls), knee pain (KP), asymptomatic radiographic OA (ROA), and symptomatic OA (SROA), [2] examine relationships between US features, pain and radiographic severity, [3] explore the relationship between change in pain and US features over a 3-month period. METHOD: Community participants were recruited into a multiple group case-control study. All underwent assessment for pain, knee radiographs and US examination for effusion, synovial hypertrophy, popliteal cysts and power Doppler (PD) signal within the synovium. A 3-month follow-up was undertaken in over half of control and SROA participants. RESULTS: 243 participants were recruited (90 controls; 59 KP; 32 ROA; 62 SROA). Effusion and synovial hypertrophy were more common in ROA and SROA participants. Severity of effusion and synovial hypertrophy were greater in SROA compared to ROA (P < 0.05). Severity of US effusion and synovial hypertrophy were correlated with radiographic severity (r = 0.6 and r = 0.7, P < 0.01) but the relationship between pain severity and US features was weak (r = 0.3, P < 0.01). In SROA participants, pain severity did not change in tandem with a change in synovial hypertrophy over time. CONCLUSION: US abnormalities are common in OA. Effusion and synovial hypertrophy were moderately correlated with radiographic severity but the relationship with pain is less strong. The degree to which these features reflect "active inflammation" is questionable and they may be better considered as part of the total organ pathology in OA. Further studies are warranted to confirm these findings.